Auxin production and plant growth promotion by Microbacterium albopurpureum sp. nov. from the rhizoplane of leafless Chiloschista parishii Seidenf. orchid - Tsavkelova, Elena A.; Volynchikova, Elena A.; Potekhina, Natalia V.; Lavrov, Konstantin V.; Avtukh, Alexander N. (Frontiers in Plant Science, 2024)
The strains of the genus Microbacterium, with more than 150 species, inhabit diverse environments; plant-associated bacteria reveal their plant growth-promoting activities due to a number of beneficial characteristics. Through the performance of diverse techniques and methods, including isolation of a novel Microbacterium strain from the aerial roots of leafless epiphytic orchid, Chiloschista parishii Seidenf., its morphological and biochemical characterization, chemotaxonomy, phylogenetic and genome analysis, as well as bioassays and estimation of its auxin production capacity, a novel strain of ET2T is described. Despite that it shared 16S rRNA gene sequence similarity of 99.79% with Microbacterium kunmingense JXJ CY 27-2T, so they formed a monophyletic group on phylogenetic trees, the two strains showed clear divergence of their genome sequences. The average nucleotide identity (ANI), average amino acid identity (AAI) and digital DNA-DNA hybridization (dDDH) values of ET2T differed greatly from phylogenetically close JXJ CY 27-2T. Based on the differences being below the threshold for species similarity, together with the unique chemotaxonomic characteristics, strain ET2T represents a novel species of the genus Microbacterium. Several genes, putatively involved in auxin biosynthesis were predicted. This strain revealed obvious plant growth-promoting activities, including diazotrophy and biosynthesis of tryptophan-dependent auxins (indole-3-acetic and indole-3-pyruvic acids). Microbial auxins directly stimulated the rhizogenesis, so that the ET2T-inoculated seeds of wheat, cucumber and garden cress showed evident promotion in their growth and development, both under optimal and under cold stress conditions. Based on phenotypic, chemotypic and genotypic evidences, the strain ET2T belongs to the genus Microbacterium, order Micrococcales, class Actinomycetes, and it represents a novel species, for which the name Microbacterium albopurpureum sp. nov. is proposed, with strain ET2T (VKPM Ac-2212, VKM Ас-2998) as the type strain.